Portulaca oleracea polysaccharides reduce serum lipid levels in aging rats by modulating intestinal microbiota and metabolites - Fu, Qiang; Huang, Hui; Ding, Aiwen; Yu, Ziqi; Huang, Yuping; Fu, Guiping; Huang, Yushan; Huang, Xiaoliu (Frontiers in Nutrition, 2022)
Metabolic diseases characterized by dyslipidemia are common health problems in elderly people. It has been demonstrated that dietary fiber intake is inversely associated with the risk of dyslipidemia. We investigated the effects of Portulaca oleracea polysaccharide (POP) on intestinal microbiota and its metabolites in aging rats using 16S rRNA sequencing and metabonomic techniques. Our results showed that POP reduced triglyceride (TG), low-density lipoprotein (LDL-C), alanine aminotransferase (ALT), gamma-glutamyl transferase (γ-GT) levels, the relative abundance of Fusobacteria, and the ratio of Firmicutes/Bacteroidetes (F/B) in aging rats. Moreover, supplementation with POP also reduced the concentrations of 5beta-cholestane-3alpha,7alpha,12alpha,25-tetrol, and vaccenic acid in lipids and lipo-like molecules, while increasing the levels of soyasapogenol E and monoacylglycerol (MG) (24:0/0:0/0:0). Our study demonstrated that the beneficial effects of POP on lipid levels in aging rats may be partially attributed to the modification of gut microbiota and related metabolites.